Impact of conflict on key agro-industries in Khartoum State, Sudan: Wheat flour milling, oil processing, and packaging - Ibrahim, Ammar; Mohamed, Shima; Abdel-Karim, Mohamed; Siddig, Khalid (International Food Policy Research Institute, 2025)
This study evaluates the effects of the ongoing armed conflict in Sudan on the agro-industrial sector in Khartoum state, with a focus on the wheat flour milling, edible oil, and packaging materials industries. The conflict, which started in April 2023, has led to widespread population displacement, destruction of infrastructure, and severe economic disruptions, especially in Khartoum, Sudan’s most industrialized and densely populated state.